Nutrients and soil structure influence furovirus infection of wheat - Gauthier, Kevin; Pankovic, Dejana; Nikolic, Miroslav; Hobert, Mirko; Germeier, Christoph U.; Ordon, Frank; Perovic, Dragan; Niehl, Annette (Frontiers in Plant Science, 2023)
Soil-borne wheat mosaic virus (SBWMV) and Soil-borne cereal mosaic virus (SBCMV), genus Furovirus, family Virgaviridae, cause significant crop losses in cereals. The viruses are transmitted by the soil-borne plasmodiophorid Polymyxa graminis. Inside P. graminis resting spores, the viruses persist in the soil for long time, which makes the disease difficult to combat. To open up novel possibilities for virus control, we explored the influence of physical and chemical soil properties on infection of wheat with SBWMV and SBCMV. Moreover, we investigated, whether infection rates are influenced by the nutritional state of the plants. Infection rates of susceptible wheat lines were correlated to soil structure parameters and nutrient contents in soil and plants. Our results show that SBWMV and SBCMV infection rates decrease the more water-impermeable the soil is and that virus transmission depends on pH. Moreover, we found that contents of several nutrients in the soil (e.g. phosphorous, magnesium, zinc) and in planta (e.g. nitrogen, carbon, boron, sulfur, calcium) affect SBWMV and SBCMV infection rates. The knowledge generated may help paving the way towards development of a microenvironment-adapted agriculture.